A study on customer service at Petronas service stations / Huda @ Norulhuda Mohamad - Mohamad, Huda @ Norulhuda (Faculty of Business and Management, 1992)
The topic of this project paper is ‘A study On Customer Service at Petronas Service Stations’. This project paper consist of the objectives of the project paper , scope of study, assumptions, methodology, findings and also conclusions and recommendations. This study will discuss about the level of customer satisfaction towards Petronas Service Stations, the appearance of Petronas Services Stations in terms of cleanliness and attractiveness of the stations and also the programs or the strategies conducted at Petronas Service Stations. The last part of this study is the conclusions and recommendations where some recommendations are recommended in order to upgrade the level of customer service at Petronas Service Stations.